2007
DOI: 10.1111/j.1464-0597.2006.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Health and Stress in English University Staff—Exposure or Vulnerability?

Abstract: In May 2002, a national benchmarking exercise of occupational stress in English Higher Education Institutions (HEIs) was carried out using the ASSET (an organisational stress screening tool), with a stratified random sample of all categories of staff. This paper presents a secondary analysis of these data by gender for full-time, permanent staff only. Results show that when differences in age and job exposure (i.e. type of university; category of employee; salary level; hours worked per week; and additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
1
37
0
9
Order By: Relevance
“…However, findings are equivocal. Most studies identify women as experiencing higher levels of stress and lower levels of job satisfaction (Wilks & Neto, 2013;Clawson, Gerstel, & Crocker, 2009;Matud, 2004;Osorio, Cohen, Escobar, Salkowski-Bartlett, & Compton, 2003;Pines & Zaidman, 2003;Tytherleigh, Jacobs, Webb, Ricketts, & Cooper, 2007). Nonetheless, some research across different countries reports that women have equal or even greater levels of overall job satisfaction compared with men (Lowe, 2007;Magee, 2013;Shields, 2006).…”
Section: A Gender Lens On Well-being At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings are equivocal. Most studies identify women as experiencing higher levels of stress and lower levels of job satisfaction (Wilks & Neto, 2013;Clawson, Gerstel, & Crocker, 2009;Matud, 2004;Osorio, Cohen, Escobar, Salkowski-Bartlett, & Compton, 2003;Pines & Zaidman, 2003;Tytherleigh, Jacobs, Webb, Ricketts, & Cooper, 2007). Nonetheless, some research across different countries reports that women have equal or even greater levels of overall job satisfaction compared with men (Lowe, 2007;Magee, 2013;Shields, 2006).…”
Section: A Gender Lens On Well-being At Workmentioning
confidence: 99%
“…On the one hand, literature from a gender perspective has examined gender differences in relation to these variables, showing that -compared to men -women in most cases experience lower job satisfaction and higher work-family conflict (Calvo-Salguero et al, 2010;Cinamon & Rich, 2002;Matud, 2004;Osorio et al, 2003;Tytherleigh et al, 2007;Van Veldhoven & Beijer, 2012). On the other hand, a body of studies has driven the attention to the impact of the occupational status, demonstrating a general positive effect of high-status occupations, even with some divergent results about the influence of status on work-family conflict (Booth & Van Ours, 2009;Calvo-Saluguero et al, 2010;Clark et al, 2008;McKinlay & Marcaeu, 2011;Salinas-Jiménez et al, 2013;Schieman et al, 2006).…”
Section: The Current Studymentioning
confidence: 99%
“…More recent research (Tytherleigh et al, 2007) found evidence that university staff exhibited significantly less organizational commitment compared to other private and public sector workers, as well as being more stressed by lack of control and resources, and worries about low pay and benefits.…”
mentioning
confidence: 99%
“…To improve understanding of work stress mechanisms and their impact on academic and non‐academic Chinese staff, research was conducted at a large, research‐intensive university in Mainland China. The aim was to evaluate and extend the ASSET (‘An Organizational Stress Screening Tool’) occupational stress model developed by Cartwright and Cooper (2002) that was also used in a national research project in British universities (Tytherleigh et al ., 2007). The study sought to evaluate the efficacy of the ASSET model for measuring the stress levels amongst academic and non‐academic staff and to explore the relationships between job stressors and individual health, job dissatisfaction and commitment.…”
mentioning
confidence: 99%